Influence of dominant environmental processes in the tropical Cuban basin Hanabanilla and reservoir on sediment composition - Labaut Betancourt, Yeny (2018)
The Hanabanilla reservoir was built in 1960 in the center-south of Cuba and is used for human supply and power generation. This research was aimed at identifying the important processes affecting sediment composition, through the analysis of particle size, and organic carbon (OC), nutrients, and major trace elements concentrations in sediment samples taken at the outlet point of the reservoir. The documentary review allowed us to identify how the nature and management of the basin and the operation of the reservoir affected sediment quality. The application of principal components analysis (PCA), and the determination of ionic relationships and correlations between the sediment quality variables, allowed for the identification of influential processes on sediment quality. Anthropic activities in the period 1960-2012 produced residues rich in OC, total phosphorus (TP) and total nitrogen (TN) that were stored in reservoir sediments. During the first years of the reservoir (1964-1976) the highest concentrations of sediment TP were recorded and the sediments functioned as a sink. The OC and TN mean concentrations were higher in the last stage of the study (2006-2012). The main influential processes on sediment composition were the operation of the reservoir, the geochemical cycle of P, the mineralization of the substances in the water column, and the weathering of silicates and the contribution of organic matter from the basin. Sediment quality data indicate that OC and TN were of allochthonous origin and TP was of autochthonous origin. Levels of sediment OC and TN also corresponded with an increase in anthropic activities in the basin.